Sağlıklı ve diyabetik kişilerden elde edilen kan hücrelerinin doku faktörü aktivitesi üzerine Candida Albicans’ın etkisinin İn Vitro incelenmesi - Güler, Seda (My University, 2011)
Bu çalışmada sağlıklı ve diyabetli kişilerin kan örneklerinden izole edilen PMNL, MNL ve trombosit hücrelerinin doku faktörü aktivitesi üzerine Candida albicans’ın invitro etkisi incelendi. İzole edilen kan hücrelerinin canlılıkları kontrol edildikten sonra sayımları yapıldı. Hücrelerin bir kısmına C. albicans süspansiyonu ilave edildi, diğer kısmına ise C. albicans süspansiyonu yerine eş değer hacimde PBS ilave edildi. Tüm hücrelerin doku faktörü aktivitesi 0., 10., 20., 30., 60., 90. ve 120. dakikalarda sağlıklı plazma kullanılarak Quick metoduna göre tayin edildi. Diyabetli kişilerin kanlarından izole edilen PMNL, MNL ve trombositlerin doku faktörü aktivitesinin sağlıklı kişilere göre ve C. albicans varlığına göre anlamlı değişiklikler gösterdiği tespit edildi. Bulgularımızın in vivo çalışmalar ile desteklenmesi durumunda kandida enfeksiyonu olan veya olmayan diyabetli hastaların tedavi planlamasına katkıda bulunacağı düşünmekteyiz. Candida albicans, diyabet, doku faktörü, lökosit, trombosit

THE INVESTIGATION OF IN VITRO EFFECT OF CANDIDA ALBICANS ON THE TISSUE FACTOR ACTIVITY OF BLOOD CELLS THAT WERE ISOLATED FROM HEALTHY AND DIABETIC INDIVIDUALS In this study, the invitro effect of Candida albicans on the tissue factor activity of the PMNL, MNL and platelet cells, that were isolated from the blood samples of healthy and diabetic individuals, were determined. The isolated blood cells were counted after the viability test has been checked. C. albicans suspension was added to one part of the cells. An equal volume phosphate buffer was added to other part of the cells instead of C. albicans suspension. Tissue factor activities of all cells were determined at 0, 10th, 20th, 30th, 60th, 90th, 120th minutes by the method of Quick by using healthy plasma. The tissue factor activity of the PMNL, MNL and platelet cells that were isolated from the diabetic individuals was found to be significantly changed when compared to the healthy individuals. Tissue factor activity of these cells was also significantly changed in the presence of C. albicans. We think that our findings will contribute to the treatment of diabetic patients with or without candida infection if supported by invivo studies. Candida albicans, diabetes, leukocyte, platelet, tissue factor
Keywords: Biyokimya